82 Management of advanced heart failure in the UK: trends in heart transplantation and mechanical circulatory support. (9th June 2011) - Emin, A; Rogers, C A; Thomas, H L; Tsui, S; Schueler, S; MacGowan, G; Simon, A; Bonser, R S; Parameshwar, J; Banner, N R
Abstract : Introduction: Patients with advanced heart failure due to systolic ventricular dysfunction require "pump replacement" therapy. Previously, heart transplantation (HTx) met this need but waiting times have increased due to shortage of donor hearts. Consequently, more patients require a ventricular assist device (VAD) as a bridge to transplant (BTT). We report UK activity, trends and outcome for HTx and BTT VAD. Methods: Data were acquired from a comprehensive national database using 3 eras for analysis: E1: 5/2002–12/2004, E2: 1/2005–12/2007 & E3: 1/2008–6/2010. Paediatric and multi-organ transplants were excluded from the transplant cohort. Patients who received prior short-term support (bridge to bridge) were excluded from the VAD group. Results: 1278 patients were listed for HTx over the 3 eras: E1 155 per year, E2 165 per year, E3 148 per year. The number of adult HTx fell from 132 per year in E1 to 94 per year in E3. The median waiting time for non-urgent HTx increased from 87 days in E1 (95%CI 55 to 119) to 321 days in E3 (95%CI 203 to 439) (p<0.001). 239 patients needed left VAD support as BTT; 75 (31%) also received a right VAD. Activity rose from 26 per year in E1 to 41 per year in E3. Device choice has changed in favour of rotary pumps; 19%, 69% and 96% for E1, E2 and E3 respectively. Median duration of VAD support increased from 84 days (IQR 20–209) in E1 to 280 days (IQR 86–661) in E3 (p<0.01). Overall survival to 1 year after VAD implant rose from 52.9% (95%CI 40 to 64) in E1 to 65.6% (95%CI 54 to 75) in E3 (p=0.10). Of the 239 patients implanted, 83 (35%) have undergone HTx, 52 (22%) are alive on VAD support & 84 (35%) died on support. Twenty were explanted following myocardial recovery; 18 of these remain alive & 2 died. Survival after HTx for patients with or without a pre-HTx VAD was 81.4% (95%CI 71 to 88) & 90.3% (95%CI 88 to 92) respectively at 30-days (p<0.01) and 80.0% (95%CI 63 to 82) & 84.3% (95%CI 82 to 87) respectively at 1-year (p<0.01). 1-year survival conditional on 30-day survival was similar with & without a pre-HTx VAD (93% vs 91%, p=0.48). Conclusion: Heart transplant activity has declined and waiting times have become prolonged leading to an increased need for bridging to transplantation. There has been a shift from volume displacement VADs to rotary blood pumps and the duration of support has increased. Post VAD survival has improved. While bridging appears to increase mortality early after HTx, longer term survival is unaffected.